A novel Radon-based multi-carrier direct sequence code division multiple access transceiver design and simulation. (11th May 2010) - Kattoush, Abbas Hasan; Al-Jawhar, Waleed Ameen; Shaheen, Ali T.
Multi-carrier direct sequence code division multiple access (MC-DS-CDMA) has emerged recently as a promising candidate for the next generation broadband mobile networks. Multipath fading channels have a severe effect on the performance of wireless communication systems even those systems that exhibit efficient bandwidth, like orthogonal frequency division multiplexing (OFDM) and MC-DS-CDMA; there is always a need for developments in the realisation of these systems as well as efficient channel estimation and equalisation methods to enable these systems to reach their maximum performance. A novel MC-DS-CDMA transceiver based on the Radon-based OFDM, which was recently proposed as a new technique in the realisation of OFDM systems, will be used here as a basic building block in the design of MC-DS-CDMA transceiver to increase the orthogonality against the multipath frequency selective fading channels. Simulation results are provided to demonstrate the significant gains in performance and simplicity due to the proposed techniques.